Stock market liquidity and macroeconomic predictability - Bay, Mingde (2013)
We investigate if liquidity risk is priced in the market from a macroeconomic perspective. We perform correlation and multi-regression analysis between the liquidity factors and the macroeconomic factors. The liquidity measures used are Pastor and Stambaugh's levels of aggregate liquidity, innovation in liquidity, and traded liquidity factor, Amihud illiquidity ratio and turnover ratio. The macroeconomic factors include the year-on-year growth rates and the cyclical component of the industrial production index, employment rate, total consumption and non-durable goods and services consumption. We find that Pastor and Stambaugh’s innovation in liquidity appears to be the most robust liquidity measure that has predictive power about the future economic growth two to three quarters later. This implies that liquidity risk is in the macroeconomy. Future economy worsens when liquidity risk is high.